A method for preparing a waterborne polyurethane resin for plastic intaglio printing ink
By placing the aminosilane end-capping reaction in an anhydrous stage during the preparation of waterborne polyurethane resin, and combining it with a differential stepwise chain extension process and the use of water-soluble aliphatic diamines, the problems of insufficient stability and adhesion of silane-modified waterborne polyurethane resin were solved, achieving high adhesion performance and high-temperature cooking resistance on non-polar films.
Patent Information
- Application Number
- CN202611392187.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-11-06
AI Technical Summary
Existing silane-modified waterborne polyurethane resins are prone to local cross-linking during preparation and storage, resulting in poor stability, low adhesion to non-polar film substrates, and insufficient high-temperature cooking adhesion.
By placing the aminosilane end-capping reaction in an anhydrous stage and combining it with a differential stepwise chain extension process in an aqueous phase, the local crosslinking and aggregation problems caused by conventional mixed chain extension are avoided by utilizing the temperature gradient and the difference in reactivity between water-soluble aliphatic diamines and isophorone diamines. Water-soluble aliphatic diamines with polyether structures are introduced to improve adhesion performance and form a dense network structure under high-temperature cooking conditions.
It improves the adhesion performance and high-temperature cooking resistance of waterborne polyurethane resin on non-polar plastic films, solves the problems of poor stability and low adhesion, and ensures that good interfacial adhesion can still be maintained after high-temperature treatment.
Smart Images

Figure CN123042276A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of water-based polymer materials technology, specifically a method for preparing water-based polyurethane resin for plastic gravure printing ink. Background Technology
[0002] With increasingly stringent environmental regulations, plastic gravure printing inks are gradually shifting towards water-based formulations, with waterborne polyurethane becoming a primary binder due to its excellent film-forming properties and flexibility. To improve the overall performance of the resin, the industry typically introduces silanes for modification. However, in actual preparation, siloxane groups are prone to premature hydrolysis and self-condensation during the aqueous dispersion stage or in conventional mixed amine chain extension processes. This not only increases the gelation rate during preparation but also leads to sudden viscosity changes or flocculation of the emulsion during long-term high-temperature storage, making it difficult to maintain a good dispersion state.
[0003] To maintain the stability of the modified emulsions, traditional synthesis processes typically require increasing the amount of anionic hydrophilic monomers such as carboxyl diols. This results in a concentration of polar centers within the polyurethane polymer chains, directly leading to higher surface tension after resin film formation. When this type of water-based ink is applied to low-surface-energy non-polar plastic films such as polypropylene and polyethylene, the high system polarity limits the effective wetting and molecular chain spreading of the resin on the substrate surface, resulting in insufficient interfacial contact and consequently lower adhesion and peel strength between the coating and the substrate.
[0004] In composite flexible packaging applications, printed films often require high-temperature cooking treatment. Because a large number of siloxane active crosslinking points in existing technologies are ineffectively consumed in the liquid phase, the resin cannot further form a dense network structure with sufficient crosslinking density when drying and curing on the substrate surface. In high-temperature boiling or steam environments, moisture easily penetrates into the coating and its interface, damaging the original physical bonds. This leads to a sharp decrease in interfacial adhesion after cooking, easily causing delamination problems. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a method for preparing waterborne polyurethane resin for plastic gravure printing ink, which solves the problems of poor stability caused by local cross-linking during the preparation and storage of existing silane-modified waterborne polyurethane resin, as well as low adhesion to non-polar film substrates and insufficient high-temperature cooking adhesion.
[0006] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a water-based polyurethane resin for plastic gravure printing ink, comprising the following steps: Poly(1,4-butanediol adipate) or polycaprolactone diol and polypropylene oxide diol are added to a reaction vessel and vacuum-mixed and dehydrated. Cool down, add isophorone diisocyanate and 2,2-dimethylolpropionic acid, or add dicyclohexylmethane diisocyanate and 2,2-dimethylolbutyric acid when using poly(1,4-butanediol adipate) diol, and add bismuth isooctanoate and butanone for prepolymerization. Cool down, and in an anhydrous environment, add 3-aminopropyltriethoxysilane dropwise when using isophorone diisocyanate, and add N-aminoethyl-3-aminopropyltrimethoxysilane dropwise when using dicyclohexylmethane diisocyanate, and keep the reaction at the temperature. Cool down, add triethylamine for neutralization, and then add deionized water dropwise for high-speed dispersion and emulsification; Reduce the stirring speed, add water-soluble aliphatic diamine and keep the reaction at a constant temperature, then add isophorone diamine and heat up to carry out the chain extension reaction; After the chain extension reaction is completed, remove the butanone under vacuum and filter. The water-soluble aliphatic diamine is prepared by copolymerization of polyethylene glycol with a number-average molecular weight Mn of 1500 g / mol or 2000 g / mol with propylene oxide end-capped by potassium hydroxide catalysis, followed by catalytic reduction amination in the presence of a supported Ni / Ru bimetallic catalyst, liquid ammonia, and hydrogen.
[0007] Preferably, when using poly(1,4-butanediol adipate), isophorone diisocyanate, 2,2-dimethylolpropionic acid, and 3-aminopropyltriethoxysilane, the reactants and their amounts include: 55-70g of poly(1,4-butanediol adipate); Polypropylene oxide glycol 30-45g; Isophorone diisocyanate 24-26g; 4-5g of 2,2-dimethylolpropionic acid; Bismuth isooctanoate 0.12-0.15g; 65-70g of methyl ethyl ketone (MEK); 1.5-2 g of 3-aminopropyltriethoxysilane; Triethylamine 3-4g; 210-220g of deionized water for high-speed dispersion and emulsification; 10-12g of water-soluble aliphatic diamine; Isophorone diamine 3-4g; The total weight of the poly(1,4-butanediol adipate) and the poly(propylene oxide) diol is 100g.
[0008] Preferably, the number-average molecular weight (Mn) of both the poly(1,4-butanediol adipate) and the poly(propylene oxide) diol is 2000 g / mol.
[0009] Preferably, the water-soluble aliphatic diamine is prepared by the following steps: Polyethylene glycol with a number average molecular weight Mn of 1500 g / mol or 2000 g / mol was added to a reaction vessel, potassium hydroxide was added as a catalyst, the temperature was raised and propylene oxide gas was introduced to carry out end-capped copolymerization reaction, and the catalyst was removed after the reaction was completed to obtain block copolymer ether with hydroxyl-terminated groups. The hydroxyl-terminated block copolymer ether was transferred to a high-pressure amination reactor, a supported Ni / Ru bimetallic catalyst was added, and liquid ammonia and hydrogen were introduced to carry out a catalytic reduction amination reaction. After the reaction was completed, the pressure was reduced, the ammonia was removed, and the catalyst was removed by filtration to obtain the water-soluble aliphatic diamine.
[0010] Preferably, the amounts of polyethylene glycol and propylene oxide gas used are 1500g and 116g, 2000g and 232g, or 2000g and 348g, respectively.
[0011] Preferably, the amount of potassium hydroxide used is 0.5 wt% of the mass of the polyethylene glycol; The end-capping copolymerization reaction is carried out at a temperature of 110-130℃, and the absolute pressure inside the reactor is 0.2-0.4MPa. The amount of the supported Ni / Ru bimetallic catalyst is 3 wt% of the mass of the hydroxyl-terminated block copolymer ether. The catalytic reduction amination reaction is carried out at a temperature of 180-220℃, a pressure of 10-15MPa, and a reaction time of 4-6 hours.
[0012] Preferably, the vacuum mixing and dehydration temperature is 90-110℃, and the dehydration time is 1-2 hours; The prepolymerization reaction is carried out at a temperature of 75-80℃ for 2-3 hours. After adding the 3-aminopropyltriethoxysilane or N-aminoethyl-3-aminopropyltrimethoxysilane, the reaction is carried out at 50°C for 20-30 minutes. The neutralization reaction is carried out at a temperature of 35-45℃, a stirring speed of 100-150 rpm, and a reaction time of 15-30 minutes.
[0013] Preferably, the stirring speed during high-speed dispersion and emulsification is 1000-2000 rpm, deionized water is added dropwise at a uniform rate, and the dispersion and emulsification time is 10-20 minutes; The temperature for vacuum removal of butanone is 45-50℃, and the removal time is 3-6 hours.
[0014] Preferably, after adding the water-soluble aliphatic diamine, the reaction temperature is 30-35°C, and the reaction is maintained at this temperature for 15-20 minutes. Then, the isophorone diamine is added and the temperature is raised to 35-45°C. The reaction is maintained at this temperature for 30-40 minutes, and the reaction temperature of the isophorone diamine is higher than that of the water-soluble aliphatic diamine.
[0015] Preferably, after reducing the stirring speed to 100-200 rpm, the water-soluble aliphatic diamine is diluted with deionized water and added slowly dropwise; The isophorone diamine was then diluted with deionized water and added dropwise.
[0016] This invention provides a method for preparing water-based polyurethane resin for plastic gravure printing ink. It has the following beneficial effects: 1. This invention improves the preparation state and storage stability of emulsions by placing the aminosilane end-capping reaction in an anhydrous stage and combining it with a differential stepwise chain extension process in an aqueous phase. The process utilizes temperature gradients and the difference in reactivity between water-soluble aliphatic diamines and isophorone diamines to isolate the chain extension reaction in sequence, avoiding the local crosslinking and aggregation problems that are easily caused by conventional mixed chain extension, controlling the gelation rate during the preparation process, so that the resulting emulsion is not prone to viscosity abrupt changes or flocculation under long-term high-temperature storage conditions.
[0017] 2. This invention improves the adhesion of polyurethane resin to non-polar plastic film surfaces by introducing a water-soluble aliphatic diamine containing a polyether structure during the chain extension stage. This specific diamine component utilizes its long-chain nonionic hydrophilic effect to assist in the emulsification of the system, reducing the amount of anionic polar monomers such as carboxyl diols required, reducing the surface tension of the resin after drying and film formation, and improving the wetting and spreading state of the coating on low surface energy substrates such as polypropylene and polyethylene, thereby enhancing the interlayer peel strength between the resin and the substrate.
[0018] 3. The multi-component synergistic design of the present invention enhances the structural stability of the resin coating under high-temperature boiling conditions. The microphase structure formed by the flexible long chain of the water-soluble aliphatic diamine in the liquid phase can provide spatial encapsulation for the siloxane end groups, inhibiting their premature loss in the aqueous phase. After the resin coating dries, the remaining siloxane groups can be fully cross-linked. Combined with the cohesive force provided by the polyester polyol in the main chain, a dense polymer network is formed inside the coating film, so that the resin can still maintain good interfacial adhesion after high-temperature boiling or boiling treatment. Attached Figure Description
[0019] Figure 1 The infrared spectrum of Test Example 1 of the present invention; Figure 2 This is the gel permeation chromatogram of Test Example 1 of the present invention; Figure 3 This is a particle size distribution diagram of the aqueous polyurethane emulsion in Test Example 2 of the present invention; Figure 4This is a graph showing the viscosity change rate during the 60°C thermal storage process of Test Example 3 of the present invention. Figure 5 This is a T-shaped peel force displacement curve on the PE non-polar film of Test Example 4 of the present invention. Detailed Implementation
[0020] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0021] Preparation Example 1: This preparation example provides a method for preparing a water-soluble aliphatic diamine with the general chemical formula H2N-CH(CH3)CH2-[OCH2CH(CH3)]a-[OCH2CH2]b-[OCH2CH(CH3)]c-NH2, where (a+c) is 4 and b is 45. The method includes the following steps: Block copolymerization: 2000g of polyethylene glycol with a number average molecular weight Mn of 2000g / mol was added to a reaction vessel, and 0.5wt% potassium hydroxide was added as a catalyst. Stirring was started and the temperature was raised to 120℃. The absolute pressure inside the reaction vessel was controlled at 0.3MPa. 232g of propylene oxide gas was introduced to carry out the end-capping copolymerization reaction. After the reaction was completed, the catalyst was removed to obtain the block copolymer ether with hydroxyl-terminated ends. Reductive amination: The above-mentioned hydroxyl-terminated block copolymer ether was transferred to a high-pressure amination reactor, and a supported Ni / Ru bimetallic catalyst of 3 wt% of the copolymer ether was added. A mixture of liquid ammonia and hydrogen was introduced, and a catalytic reductive amination reaction was carried out at 200°C and 12 MPa for 5 hours. After the reaction was completed, the catalyst was removed by depressurization, deammoniation and filtration to obtain the water-soluble aliphatic diamine.
[0022] Preparation Example 2: This preparation example provides a method for preparing a water-soluble aliphatic diamine with the general chemical formula H2N-CH(CH3)CH2-[OCH2CH(CH3)]a-[OCH2CH2]b-[OCH2CH(CH3)]c-NH2, where (a+c) is 2 and b is 34. The method includes the following steps: Block copolymerization: 1500g of polyethylene glycol with a number-average molecular weight Mn of 1500g / mol was added to a reaction vessel, and 0.5wt% potassium hydroxide was added as a catalyst. Stirring was started and the temperature was raised to 110℃. The absolute pressure inside the reaction vessel was controlled at 0.2MPa. 116g of propylene oxide gas was introduced to carry out the end-capping copolymerization reaction. After the reaction was completed, the catalyst was removed to obtain the block copolymer ether with hydroxyl-terminated hydroxyl groups. Reductive amination: The above-mentioned hydroxyl-terminated block copolyether was transferred to a high-pressure amination reactor, and a supported Ni / Ru bimetallic catalyst of 3 wt% of the copolyether was added. A mixture of liquid ammonia and hydrogen was introduced, and a catalytic reductive amination reaction was carried out at 180°C and 10 MPa for 6 hours. After the reaction was completed, the catalyst was removed by depressurization, deammoniation and filtration to obtain the water-soluble aliphatic diamine.
[0023] Preparation Example 3: This preparation example provides a method for preparing a water-soluble aliphatic diamine with the general chemical formula H2N-CH(CH3)CH2-[OCH2CH(CH3)]a-[OCH2CH2]b-[OCH2CH(CH3)]c-NH2, where (a+c) is 6 and b is 45. The method includes the following steps: Block copolymerization: 2000g of polyethylene glycol with a number-average molecular weight Mn of 2000g / mol was added to a reactor, and 0.5wt% potassium hydroxide was added as a catalyst. Stirring was started and the temperature was raised to 130℃. The absolute pressure inside the reactor was controlled at 0.4MPa. 348g of propylene oxide gas was introduced to carry out the end-capping copolymerization reaction. After the reaction was completed, the catalyst was removed to obtain the block copolymer ether with hydroxyl-terminated ends. Reductive amination: The above-mentioned hydroxyl-terminated block copolymer ether was transferred to a high-pressure amination reactor, and a supported Ni / Ru bimetallic catalyst of 3 wt% of the copolymer ether was added. A mixture of liquid ammonia and hydrogen was introduced, and a catalytic reductive amination reaction was carried out at 220°C and 15 MPa for 4 hours. After the reaction was completed, the catalyst was removed by depressurization, deammoniation and filtration to obtain the water-soluble aliphatic diamine.
[0024] Example 1: This embodiment provides a method for preparing water-based polyurethane resin for plastic gravure printing ink, including the following steps: Vacuum mixing and dehydration: 55g of poly(1,4-butanediol adipate) diol with a number-average molecular weight (Mn) of 2000g / mol and 45g of poly(propylene oxide) diol with a number-average molecular weight (Mn) of 2000g / mol were added to a reaction vessel equipped with a jacketed heating and reflux condenser. Stirring was started, the temperature was raised to 100℃, and dehydration was carried out under vacuum conditions of -0.095MPa absolute pressure for 1.5 hours. The vacuum was then released and the mixture was cooled for later use. Prepolymerization reaction: When the temperature inside the reactor drops to 60℃, add 24g of isophorone diisocyanate, 4g of 2,2-dimethylolpropionic acid, 0.12g of bismuth isooctanoate and 65g of butanone in sequence. Adjust the jacket cooling water to maintain the reaction temperature inside the reactor at 78℃ and keep the reaction at this temperature for 2.5 hours. Anhydrous silane end-capping: Cool the above prepolymer system to 50°C, and slowly add 1.5g of 3-aminopropyltriethoxysilane in an anhydrous environment. Keep the reaction at 50°C for 25 minutes. Cooling and neutralization to form salt: Further reduce the temperature inside the vessel to 40°C, add 3g of triethylamine, and neutralize the reaction for 20 minutes with a stirring speed of 120rpm. High-speed dispersion and emulsification: 210g of deionized water is added dropwise to the reaction vessel at a uniform rate, and the stirring speed is increased to 1500rpm. High-speed dispersion and emulsification is carried out for 15 minutes to form an oil-in-water polyurethane emulsion. Chain extension after differential stepwise reaction in aqueous phase: The stirring speed was reduced to 150 rpm, and 10 g of the water-soluble aliphatic diamine obtained in Preparation Example 1 was diluted with 10 g of deionized water and slowly added dropwise to the emulsion. The temperature inside the reactor was controlled at 32 °C, and the reaction was maintained at this temperature for 18 minutes. Subsequently, 3 g of isophorone diamine was diluted with a small amount of deionized water and added dropwise to the emulsion. The temperature inside the reactor was raised to 40 °C, and the reaction was maintained at this temperature for 35 minutes. Vacuum desolventization: After the chain extension reaction is completed, the temperature of the reactor is controlled at 48℃, and the butanone is removed by vacuuming under an absolute pressure of -0.09MPa for 4 hours. The product is then discharged and filtered to obtain the final product.
[0025] Example 2: This embodiment provides a method for preparing water-based polyurethane resin for plastic gravure printing ink, including the following steps: Vacuum mixing and dehydration: 40g of polycaprolactone diol with a number average molecular weight Mn of 2000g / mol and 60g of polypropylene oxide diol with a number average molecular weight Mn of 2000g / mol were added to a reaction vessel equipped with a jacketed heating and reflux condenser. Stirring was started, the temperature was raised to 90℃, and dehydration was carried out under vacuum conditions of absolute pressure of -0.09MPa for 2 hours. The vacuum was then released and the mixture was cooled for later use. Prepolymerization reaction: When the temperature inside the reactor drops to 60°C, add 22g of isophorone diisocyanate, 3g of 2,2-dimethylolpropionic acid, 0.1g of bismuth isooctanoate and 60g of butanone in sequence. Adjust the jacket cooling water to maintain the reaction temperature inside the reactor at 75°C and keep the reaction at this temperature for 3 hours. Anhydrous silane end-capping: Cool the above prepolymer system to 50°C, and slowly add 1g of 3-aminopropyltriethoxysilane in an anhydrous environment. Keep the reaction at 50°C for 20 minutes. Cooling and neutralization to form salt: Further reduce the temperature inside the vessel to 35°C, add 2g of triethylamine, and neutralize the reaction for 30 minutes with a stirring speed of 100rpm. High-speed dispersion and emulsification: 200g of deionized water is added dropwise to the reaction vessel at a uniform rate, and the stirring speed is increased to 1000rpm. High-speed dispersion and emulsification is carried out for 20 minutes to form an oil-in-water polyurethane emulsion. Chain extension after differential stepwise reaction in aqueous phase: The stirring speed was reduced to 100 rpm, and 8 g of the water-soluble aliphatic diamine obtained in Preparation Example 2 was diluted with 10 g of deionized water and slowly added dropwise to the emulsion. The temperature inside the reactor was controlled at 30°C, and the reaction was maintained at this temperature for 20 minutes. Subsequently, 3 g of isophorone diamine was diluted with a small amount of deionized water and added dropwise to the emulsion. The temperature inside the reactor was raised to 35°C, and the reaction was maintained at this temperature for 40 minutes. Vacuum desolventization: After the chain extension reaction is completed, the temperature of the reactor is controlled at 45℃, and the butanone is removed by vacuuming under an absolute pressure of -0.095MPa for 6 hours. The product is then discharged and filtered to obtain the final product.
[0026] Example 3: This embodiment provides a method for preparing water-based polyurethane resin for plastic gravure printing ink, including the following steps: Vacuum mixing and dehydration: 70g of poly(1,4-butanediol adipate) diol with a number average molecular weight Mn of 2000g / mol and 30g of poly(propylene oxide) diol with a number average molecular weight Mn of 2000g / mol were added to a reaction vessel equipped with a jacketed heating and reflux condenser. Stirring was started, the temperature was raised to 110℃, and dehydration was carried out under vacuum conditions of -0.098MPa absolute pressure for 1 hour. The vacuum was then released and the mixture was cooled for later use. Prepolymerization reaction: When the temperature inside the reactor drops to 60°C, add 26g of isophorone diisocyanate, 5g of 2,2-dimethylolpropionic acid, 0.15g of bismuth isooctanoate and 70g of butanone in sequence. Adjust the jacket cooling water to maintain the reaction temperature inside the reactor at 80°C and keep the reaction at this temperature for 2 hours. Anhydrous silane end-capping: Cool the above prepolymer system to 50°C, and slowly add 2g of 3-aminopropyltriethoxysilane in an anhydrous environment. Keep the reaction at 50°C for 30 minutes. Cooling and neutralization to form salt: Further reduce the temperature inside the vessel to 45°C, add 4g of triethylamine, and neutralize the reaction for 15 minutes with a stirring speed of 150rpm. High-speed dispersion and emulsification: 220g of deionized water is added dropwise to the reaction vessel at a uniform rate, and the stirring speed is increased to 2000rpm. High-speed dispersion and emulsification is carried out for 10 minutes to form an oil-in-water polyurethane emulsion. Chain extension after differential stepwise reaction in aqueous phase: The stirring speed was reduced to 200 rpm, and 12 g of the water-soluble aliphatic diamine obtained in Preparation Example 3 was diluted with 10 g of deionized water and slowly added dropwise to the emulsion. The temperature inside the reactor was controlled at 35°C and the reaction was maintained at this temperature for 15 minutes. Subsequently, 4 g of isophorone diamine was diluted with a small amount of deionized water and added dropwise to the emulsion. The temperature inside the reactor was raised to 45°C and the reaction was maintained at this temperature for 30 minutes. Vacuum desolventization: After the chain extension reaction is completed, the temperature of the reactor is controlled at 50℃, and the butanone is removed by vacuuming under an absolute pressure of -0.08MPa for 3 hours. The product is then discharged and filtered to obtain the final product.
[0027] Example 4: This embodiment provides a method for preparing water-based polyurethane resin for plastic gravure printing ink, including the following steps: Vacuum mixing and dehydration: 55g of poly(1,4-butanediol adipate) diol with a number-average molecular weight (Mn) of 2000g / mol and 45g of poly(propylene oxide) diol with a number-average molecular weight (Mn) of 2000g / mol were added to a reaction vessel equipped with a jacketed heating and reflux condenser. Stirring was started, the temperature was raised to 100℃, and dehydration was carried out under vacuum conditions of -0.095MPa absolute pressure for 1.5 hours. The vacuum was then released and the mixture was cooled for later use. Prepolymerization reaction: When the temperature inside the reactor drops to 60℃, add 26g of dicyclohexylmethane diisocyanate, 4g of 2,2-dihydroxymethylbutyric acid, 0.12g of bismuth isooctanoate and 65g of butanone in sequence. Adjust the jacket cooling water to maintain the reaction temperature inside the reactor at 78℃ and keep the reaction at this temperature for 2.5 hours. Anhydrous silane end-capping: Cool the above prepolymer system to 50°C, and slowly add 1.5g of N-aminoethyl-3-aminopropyltrimethoxysilane in an anhydrous environment. Keep the reaction at 50°C for 25 minutes. Cooling and neutralization to form salt: Further reduce the temperature inside the vessel to 40°C, add 3g of triethylamine, and neutralize the reaction for 20 minutes with a stirring speed of 120rpm. High-speed dispersion and emulsification: 210g of deionized water is added dropwise to the reaction vessel at a uniform rate, and the stirring speed is increased to 1500rpm. High-speed dispersion and emulsification is carried out for 15 minutes to form an oil-in-water polyurethane emulsion. Chain extension after differential stepwise reaction in aqueous phase: The stirring speed was reduced to 150 rpm, and 10 g of the water-soluble aliphatic diamine obtained in Preparation Example 1 was diluted with 10 g of deionized water and slowly added dropwise to the emulsion. The temperature inside the reactor was controlled at 32 °C, and the reaction was maintained at this temperature for 18 minutes. Subsequently, 3 g of isophorone diamine was diluted with a small amount of deionized water and added dropwise to the emulsion. The temperature inside the reactor was raised to 40 °C, and the reaction was maintained at this temperature for 35 minutes. Vacuum desolventization: After the chain extension reaction is completed, the temperature of the reactor is controlled at 48℃, and the butanone is removed by vacuuming under an absolute pressure of -0.09MPa for 4 hours. The product is then discharged and filtered to obtain the final product.
[0028] Comparative Example 1: Compared with Example 1, the difference is that no water-soluble aliphatic diamine was added. In order to ensure emulsification stability, the amount of 2,2-dimethylolpropionic acid in the prepolymerization reaction was increased to 8g, and the amount of triethylamine in the neutralization step was correspondingly increased to 5.5g. All other aspects are the same.
[0029] Comparative Example 2: Compared with Example 1, the difference is that the feeding sequence in the chain extension step after differential speed stepping in the aqueous phase is changed. The water-soluble aliphatic diamine and isophorone diamine are mixed and then added dropwise to the emulsion at one time to carry out the chain extension reaction. All other steps are the same.
[0030] Comparative Example 3: Compared with Example 1, the difference is that the anhydrous silane end-capping operation of the anhydrous silane end-capping step is omitted, and an equal amount of 3-aminopropyltriethoxysilane is transferred to the aqueous phase in the differential stepwise chain extension step, and is added dropwise to the aqueous phase simultaneously with the water-soluble aliphatic diamine. All other aspects are the same.
[0031] Comparative Example 4: Compared with Example 1, the difference is that: no water-soluble aliphatic diamine was added in the chain extension step after differential stepping in the aqueous phase; isophorone diamine was directly used for a single-step rigid chain extension in the aqueous phase. All other aspects are the same.
[0032] Test Example 1: Infrared spectroscopy tests were conducted using samples taken at the end of the prepolymerization reaction in Example 1, samples taken at the end of the anhydrous silane end-capping reaction, and the final aqueous polyurethane film that had been prepared and cured at room temperature. The samples were coated onto potassium bromide plates, and the solvent was removed in a vacuum drying oven to form a film. Fourier transform infrared spectroscopy was used to measure the infrared spectroscopy results in the range of 4000 to 4000 cm⁻¹. -1 A full-spectrum scan was performed within the wavenumber range, and the infrared transmission spectrum curve was recorded.
[0033] The aqueous polyurethane resins prepared in Example 1 and Comparative Example 2 were used as experimental subjects in gel permeation chromatography. The resin samples were dissolved in chromatographic grade tetrahydrofuran to prepare a test solution with a mass concentration of approximately 3 mg / mL, which was then filtered through a 0.22 μm organic microporous membrane. The test was performed using a gel permeation chromatograph equipped with a refractive index detector. The mobile phase was tetrahydrofuran, the flow rate was set to 1.0 mL / min, and the column temperature was maintained at 35 °C. Calibration curves were plotted using monodisperse polystyrene standards of different molecular weights. The number-average molecular weight (Mn), weight-average molecular weight (Mw), and polydispersity index (PDI) of the samples were calculated based on the retention time.
[0034] Table 1. Molecular weight and distribution test data of Example 1 and Comparative Example 2 Experimental subjects Number-average molecular weight Mn (g / mol) Weight-average molecular weight Mw (g / mol) Multidispersive Index (PDI) Example 1 23145 47216 2.04 Comparative Example 2 11542 79438 6.88
[0035] Summary: Based on Table 1 and Figure 1 The test results, in Example 1, showed that the infrared spectrum of the sample taken at the end of the prepolymerization reaction was at 2270 cm⁻¹. -1 An absorption peak for isocyanate groups appeared nearby; after the anhydrous silane end-capping step, the relative intensity of this absorption peak decreased, which is consistent with the process of partial bonding reaction of the end groups. In the final cured film, this characteristic isocyanate absorption peak was not significantly retained, and it also appeared at 1640 cm⁻¹. -1 and 1080cm -1 The corresponding absorption peaks appear nearby, which correspond to the characteristic absorption bands of the urea bonds generated during the aqueous chain extension stage and the Si-O-Si structure formed by the hydrolysis and condensation of silane.
[0036] Figure 2 As shown in Table 1, the chromatographic curve of Example 1 exhibits monodisperse characteristics, with a relatively low polydispersity index and a concentrated molecular weight distribution. Comparative Example 2, after chain extension using a single-stage mixing process, shows a chromatographic curve with multiple peaks, a higher polydispersity index, and a lower number-average molecular weight than Example 1. This comparison indicates that the mixed addition of large-molecule and small-molecule diamines causes uneven crosslinking within the system. The above test data reflect that the steric hindrance differential chain extension process of this invention helps control the uniform growth of polymer molecular weight. Test Example 2: The experimental subjects for dynamic light scattering tests were the aqueous polyurethane emulsions prepared after the solvent removal step in Examples 1, 1, and 3. Each emulsion sample was taken and diluted with deionized water with a conductivity of less than 5 μS / cm to a mass fraction of 0.1% as the test solution.
[0037] The test solution was injected into a quartz cuvette and placed in the sample chamber of the dynamic light scattering instrument. The test temperature was set to 25℃, the solvent refractive index to be 1.33, and the equilibration time to be 120 seconds.
[0038] The instrument was activated to acquire laser scattering signals. Each sample was measured three times consecutively, with each measurement lasting 60 seconds. The instrument then used a cumulative method to fit the correlation function, obtaining the Z-mean particle size and polydispersity index of the samples, and recording the particle size distribution curves.
[0039] Table 2. Emulsion particle size test data of Example 1, Comparative Examples 1 and 3 Experimental subjects Z-average particle size (nm) Particle size polydispersity index (PDI) Example 1 82.6 0.131 Comparative Example 1 38.4 0.165 Comparative Example 3 412.8 0.594
[0040] Summary: Based on Table 2 and Figure 3 The test results show that the emulsion in Example 1 has a relatively narrow particle size distribution and a low polydispersity coefficient, exhibiting monodisperse characteristics. This result is consistent with the microphase encapsulation design in which the nonionic hydrophilic segments of water-soluble aliphatic diamine, combined with a small amount of anionic groups, participate in the water dispersion process. In Comparative Example 1, the amount of dimethylolpropionic acid was increased, resulting in a relatively high density of anionic groups in the system, and the average particle size after dispersion showed a trend of decreasing compared to Example 1. In Comparative Example 3, where aminosilane was directly added to the aqueous phase without an anhydrous silane end-capping step, the particle size distribution curve shifted towards larger sizes, exhibiting a broadened distribution and multiple peaks, with both the Z-average particle size and polydispersity coefficient showing high values. This phenomenon suggests that the aminosilane underwent a hydrolysis-condensation reaction in the aqueous phase, thereby affecting the dispersion state of the latex particles. The above comparative results reflect the influence of the feeding sequence process on controlling side reactions and maintaining the microscopic stability of the emulsion.
[0041] Test Example 3: The gelation rate test and apparent state observation were conducted on the initial state of the aqueous polyurethane emulsions of Examples 1-4 and Comparative Examples 1-4 after the completion of the aqueous chain extension and solvent removal steps. During the discharge process from the reactor, each group of emulsions was filtered through a 200-mesh standard stainless steel filter. The residue on the filter screen and the adhering agglomerates on the reactor agitator shaft and reactor wall were collected, repeatedly washed with deionized water, and then dried in a vacuum drying oven at 105°C until constant weight. The gelation rate of each sample was obtained by calculating the percentage of the mass of the dried residue to the total mass of the theoretical resin solids in the batch, and the apparent state of the filtered emulsions was recorded.
[0042] The experimental subjects for the thermal storage stability test were the emulsions of each embodiment and comparative example after filtration as described above. Each group of samples was placed into a 250mL sealed glass bottle, and the rotational viscosity at initial room temperature was measured and recorded. The sealed bottles were then stored in a 60°C constant temperature oven. Samples were taken every 5 days during storage, and their viscosity was measured after the samples returned to room temperature. If the sample exhibited stratification, flocculation, or a viscosity exceeding three times the initial value, it was considered a thermal storage failure, and the corresponding failure time was recorded.
[0043] Table 3. Gelation rate and thermal storage stability test data of the examples and comparative examples Experimental subjects gelation rate (%) Appearance of the emulsion after filtration Failure time (days) during 60℃ hot storage Example 1 0.12 bluish translucent homogeneous liquid >30 Example 2 0.25 bluish translucent homogeneous liquid >30 Example 3 0.18 bluish translucent homogeneous liquid >30 Example 4 0.21 bluish translucent homogeneous liquid >30 Comparative Example 1 0.15 bluish translucent homogeneous liquid >30 Comparative Example 2 5.82 Slightly turbid liquid with particles 15 Comparative Example 3 24.37 Contains a lot of viscous lumps, causing filter clogging. No storage test was conducted. Comparative Example 4 1.14 Milky white liquid with a bluish tint 20
[0044] Summary: Based on Table 3 and Figure 4 The test results showed that the gel rates of Examples 1-4 were relatively low, and their viscosity changes were relatively gradual under high-temperature storage conditions of 60°C. This suggests that the differential stepwise chain extension process helps to regulate the reaction process, and the anhydrous silane end-capping step plays a certain role in slowing down the self-condensation of siloxanes in the aqueous phase. Comparative Example 2 used a mixed chain extension method, and the measured gel rate was relatively high, with a rapid increase in viscosity during hot storage. This is related to the uneven local reaction caused by the difference in the reactivity of different amine monomers. Comparative Example 3 did not use anhydrous silane end-capping, but instead added aminosilane directly to the aqueous phase. Its gel rate was high and obvious agglomeration occurred, indicating that silane is more prone to hydrolysis and condensation side reactions under this feeding method. Comparative Example 4 did not use a specific water-soluble aliphatic diamine, and a rapid increase in viscosity occurred in the later stage of hot storage. This is related to the lack of long flexible chain segments in the system, which led to the slow reaction of some siloxane groups in the aqueous phase. The above test results reflect, from a macroscopic process perspective, the impact of specific components and timing processes in this scheme on maintaining the emulsion preparation state and storage stability.
[0045] Test Example 4: The waterborne polyurethane emulsions prepared in Examples 1 to 4, Comparative Example 1, and Comparative Example 4 were used for the non-polar substrate adhesion performance test. Comparative Examples 2 and 3 were not included in this test because their gelation rates were too high or they could not form stable emulsions. Commercially available BOPP and polyethylene (PE) films with a thickness of 30 μm were selected as non-polar plastic substrates.
[0046] Adjust the solid content of each emulsion sample to approximately 30% using deionized water. Apply the test solution to the test surface of the substrate using a No. 4 wire rod coater. Place the coated film in a 60°C forced-air drying oven for 10 minutes, controlling the dry film thickness within the range of 3 to 5 μm.
[0047] After the film samples were placed in an environment of 25°C and 50% relative humidity for 24 hours, the cross-cut adhesion test was performed. One hundred 1mm × 1mm grids were drawn on the coating surface using a standard cross-cut knife, with the scratches reaching the substrate. Test tape was applied to the grid area, air bubbles were removed, and the area was allowed to stand for 60 seconds before the tape was peeled off at an angle close to 60 degrees. The peeling grade of the coating in the grid area was recorded according to ASTM D3359 standard, with 5B indicating no peeling and 0B indicating a peeling area greater than 65%.
[0048] Peel strength test: The coated and dried film sample was heat-compressed to the surface of another uncoated substrate of the same specification. The heat sealer temperature was set to 120℃, the pressure to 0.3MPa, and the heat-compression time to 1.5 seconds. After cooling, the sample was cut into strips with a width of 15mm. A T-shaped peel test was performed using a universal testing machine at a tensile rate of 300mm / min. The load-displacement curve during the test was recorded, and the average peel force at failure was calculated.
[0049] Table 4. Adhesion performance test data of the examples and comparative examples on the surface of non-polar thin films. Experimental subjects BOPP adhesion rating PE cross-cut adhesion rating Peel strength of BOPP substrate (N / 15mm) Peel strength of PE substrate (N / 15mm) Example 1 5B 4B 1.83 1.45 Example 2 4B 5B 1.76 1.58 Example 3 5B 5B 1.95 1.62 Example 4 4B 4B 1.62 1.34 Comparative Example 1 1B 0B 0.52 0.28 Comparative Example 4 3B 2B 0.96 0.81
[0050] Summary: Based on Table 4 and Figure 5 The test results show that the polyurethane resins prepared in Examples 1-4 exhibited relatively high cross-cut adhesion ratings and T-peel strengths on BOPP and PE non-polar films. Figure 4 As shown in the peel force displacement curve, Example 1 reaches a stable state relatively quickly during the tensile peeling process and can maintain a high peel force. This phenomenon suggests that the design of reducing the polarity of the system through specific components helps to improve the adhesion performance of the material on low surface energy substrates. In Comparative Example 1, the amount of dimethylolpropionic acid was increased, and the polar centers of the anionic carboxylate in the system were relatively dense, resulting in a higher surface tension of the coating film.
[0051] During the coating and wetting process, the higher polarity limits the spread of the coating molecular chains on the polyolefin surface, which is reflected in the test as a decrease in peel strength and an increase in the area of cross-linking failure. The example introduces a water-soluble aliphatic diamine to assist the emulsification process at a lower carboxylate content. The relative decrease in system polarity after film formation helps improve the matching degree of interfacial tension. Comparative Example 4 lacks the participation of corresponding long flexible segments. The change in system state causes partial cross-linking of the siloxane end groups before drying. The increased molecular chain rigidity has a certain impact on the interfacial bonding of the film surface, and its adhesion test results are lower than those of the example group.
Claims
1. A method for preparing a waterborne polyurethane resin for plastic gravure printing ink, characterized by, Includes the following steps: Poly(1,4-butanediol adipate) or polycaprolactone diol and polypropylene oxide diol are added to a reaction vessel and vacuum-mixed and dehydrated. Cool down, add isophorone diisocyanate and 2,2-dimethylolpropionic acid, or add dicyclohexylmethane diisocyanate and 2,2-dimethylolbutyric acid when using poly(1,4-butanediol adipate) diol, and add bismuth isooctanoate and butanone for prepolymerization. Cool down, and in an anhydrous environment, add 3-aminopropyltriethoxysilane dropwise when using isophorone diisocyanate, and add N-aminoethyl-3-aminopropyltrimethoxysilane dropwise when using dicyclohexylmethane diisocyanate, and keep the reaction at the temperature. Cool down, add triethylamine for neutralization, and then add deionized water dropwise for high-speed dispersion and emulsification; Reduce the stirring speed, add water-soluble aliphatic diamine and keep the reaction at a constant temperature, then add isophorone diamine and heat up to carry out the chain extension reaction; After the chain extension reaction is completed, remove the butanone under vacuum and filter. The water-soluble aliphatic diamine is prepared by copolymerization of polyethylene glycol with a number-average molecular weight Mn of 1500 g / mol or 2000 g / mol with propylene oxide end-capped by potassium hydroxide catalysis, followed by catalytic reduction amination in the presence of a supported Ni / Ru bimetallic catalyst, liquid ammonia, and hydrogen.
2. The method of preparing a waterborne polyurethane resin for a plastic gravure printing ink according to claim 1, characterized by, When using poly(1,4-butanediol adipate), isophorone diisocyanate, 2,2-dimethylolpropionic acid, and 3-aminopropyltriethoxysilane, the reactants and their amounts include: 55-70g of poly(1,4-butanediol adipate); Polypropylene oxide glycol 30-45g; Isophorone diisocyanate 24-26g; 4-5g of 2,2-dimethylolpropionic acid; Bismuth isooctanoate 0.12-0.15g; 65-70g of methyl ethyl ketone (MEK); 1.5-2 g of 3-aminopropyltriethoxysilane; Triethylamine 3-4g; 210-220g of deionized water for high-speed dispersion and emulsification; 10-12g of water-soluble aliphatic diamine; Isophorone diamine 3-4g; The total weight of the poly(1,4-butanediol adipate) and the poly(propylene oxide) diol is 100g.
3. The method of preparing a waterborne polyurethane resin for a plastic gravure printing ink according to claim 2, characterized by, The number-average molecular weight (Mn) of both the poly(1,4-butanediol adipate) and the poly(propylene oxide) diol is 2000 g / mol.
4. The method of preparing an aqueous polyurethane resin for a plastic gravure printing ink according to claim 1, characterized by, The water-soluble aliphatic diamine is prepared by the following steps: Polyethylene glycol with a number average molecular weight Mn of 1500 g / mol or 2000 g / mol was added to a reaction vessel, potassium hydroxide was added as a catalyst, the temperature was raised and propylene oxide gas was introduced to carry out end-capped copolymerization reaction, and the catalyst was removed after the reaction was completed to obtain block copolymer ether with hydroxyl-terminated groups. The hydroxyl-terminated block copolymer ether was transferred to a high-pressure amination reactor, a supported Ni / Ru bimetallic catalyst was added, and liquid ammonia and hydrogen were introduced to carry out a catalytic reduction amination reaction. After the reaction was completed, the pressure was reduced, the ammonia was removed, and the catalyst was removed by filtration to obtain the water-soluble aliphatic diamine.
5. The method of preparing a waterborne polyurethane resin for a plastic gravure printing ink according to claim 4, characterized by, The amounts of polyethylene glycol and propylene oxide gas used are 1500g and 116g, 2000g and 232g, or 2000g and 348g, respectively.
6. The method of preparing an aqueous polyurethane resin for a plastic gravure printing ink according to claim 4, characterized by, The amount of potassium hydroxide used is 0.5 wt% of the mass of the polyethylene glycol; The end-capping copolymerization reaction is carried out at a temperature of 110-130℃, and the absolute pressure inside the reactor is 0.2-0.4MPa. The amount of the supported Ni / Ru bimetallic catalyst is 3 wt% of the mass of the hydroxyl-terminated block copolymer ether. The catalytic reduction amination reaction is carried out at a temperature of 180-220℃, a pressure of 10-15MPa, and a reaction time of 4-6 hours.
7. The method for preparing a water-based polyurethane resin for plastic gravure printing ink according to claim 1, characterized in that, The vacuum mixing and dehydration temperature is 90-110℃, and the dehydration time is 1-2 hours; The prepolymerization reaction is carried out at a temperature of 75-80℃ for 2-3 hours. After adding the 3-aminopropyltriethoxysilane or N-aminoethyl-3-aminopropyltrimethoxysilane, the reaction is carried out at 50°C for 20-30 minutes. The neutralization reaction is carried out at a temperature of 35-45℃, a stirring speed of 100-150 rpm, and a reaction time of 15-30 minutes.
8. The method for preparing a water-based polyurethane resin for plastic gravure printing ink according to claim 1, characterized in that, The stirring speed during high-speed dispersion and emulsification is 1000-2000 rpm, deionized water is added dropwise at a uniform rate, and the dispersion and emulsification time is 10-20 minutes; The temperature for vacuum removal of butanone is 45-50℃, and the removal time is 3-6 hours.
9. The method for preparing a water-based polyurethane resin for plastic gravure printing ink according to claim 1, characterized in that, After adding the water-soluble aliphatic diamine, the reaction temperature is 30-35℃, and the reaction is maintained at this temperature for 15-20 minutes. Then, the isophorone diamine is added and the temperature is raised to 35-45°C. The reaction is maintained at this temperature for 30-40 minutes, and the reaction temperature of the isophorone diamine is higher than that of the water-soluble aliphatic diamine.
10. The method for preparing a water-based polyurethane resin for plastic gravure printing ink according to claim 1, characterized in that, After reducing the stirring speed to 100-200 rpm, the water-soluble aliphatic diamine was diluted with deionized water and added slowly dropwise. The isophorone diamine was then diluted with deionized water and added dropwise.
